ISLAMIC LAW REVIEW OF MONOPOLY PRACTICES IN MODERN ECONOMICS - Muhammad Achyar; Fahmi, Chairul (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
This research aims to analyse how the mechanism of modern economic monopoly practices, and how its application can prevent harmful business practices, and support the creation of a fairer and more ethical market in accordance with Islamic teachings. This research uses a qualitative approach with a literature study method (library research). This approach was chosen because it is in accordance with the purpose of this research, which is to evaluate monopoly practices in the context of modern economics based on the perspective of Islamic law. The results show that the rapid development of the modern economy and the phenomenon of monopoly have become one of the issues that attract the attention of economists, legislators, and legal scholars, including Islamic legal experts. In the context of Islamic law, monopolies that harm the interests of society are considered immoral and prohibited, as they can lead to economic injustice and oppression of consumers. Islam emphasises the importance of fairness, balance and protection of individual rights in every economic transaction. Islamic law, through concepts such as hisbah (market supervision) and ihtikar (prohibition of hoarding goods to raise prices), prescribes those economic activities be conducted in a fair and transparent manner. Therefore, monopolistic practices that result in market imbalances and harm society should be avoided.